Empowerment of care home staff through effective collaboration with healthcare. Issue 1 (2nd January 2023) - Woodward, Amelia; Ruston, Annmarie
ABSTRACT: Integrative local health delivery models in the UK, under the framework of Enhanced Health in Care Homes (EHICH), have been developed to improve joint working between health and social care to benefit the patient. Despite this drive toward health and social care integration, research on the barriers, facilitators, and impact of partnership working on role of care home staff is underdeveloped. This study set out to explore views on how closer working between health and social care can impact on the role of care home staff and any barriers to effective integration. Staff from 25 care homes and GPs from their partnered practices were interviewed to explore the impact of the partnership. Homes receiving regular visits from the same health professional found the relationship between the two sectors had benefitted both residents and staff. The development of trusting relationships, access to support and information, and recognition and respect were all seen as facilitating the partnership and enhancing patient care. Regular and effective interactions with health-care professionals were key and had the potential to empower and increase confidence of care home staff in their role around health care. Factors negatively impacting on strength of relationship such as visits by inconsistent professional and high turnover of care home staff were a barrier to successful partnerships. Experiences of poor interactions with those from health-care services where there was an absence of a trusting relationship were disempowering to care home staff and remain a barrier to effective wider health and social care collaboration.